Nueva localidad de presencia de Xiphion boissieri (Henriq.) Rodion. en Galicia. A new locality for Xiphion boissieri (Henriq.) Rodion. in Galicia - Mouriño, Jorge; Romeu, Manuel; Salvadores, Rafael (Acta Botanica Malacitana, 2012)
A new locality for Xiphion boissieri (Henriq.) Rodion. in Galicia Palabras clave. Galicia, Xiphion boissieri, nueva localidad Key words. Galicia, Xiphion boissieri, new localit